2015
DOI: 10.1111/ced.12635
|View full text |Cite
|
Sign up to set email alerts
|

Galactomyces fermentation filtrate prevents T helper 2‐mediated reduction of filaggrin in an aryl hydrocarbon receptor‐dependent manner

Abstract: SummaryBackground. The aryl hydrocarbon receptor (AhR) recognizes diverse small molecules such as dioxins, tryptophan photoproducts and phytochemicals. It also plays crucial roles in epidermal homeostasis by upregulating epidermal barrier proteins. In preliminary screening, we found that Galactomyces fermentation filtrate (GFF), a cosmetic compound, was capable of activating AhR. Aim. To examine whether GFF upregulates the expression of the filaggrin and loricrin genes, FLG and LOR, in an AhR-dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 19 publications
6
66
0
Order By: Relevance
“…It has been increasingly used for cosmetic purposes [57]. Galactomyces fermentation filtrate is also an AHR-stimulant generally used in cosmetics [58]. Interestingly, epigallocatechin gallate and Galactomyces fermentation filtrate exhibit synergistic antioxidant activity against TNFα-induced ROS production (Figure 5).…”
Section: Phytogenic Antioxidantsmentioning
confidence: 99%
“…It has been increasingly used for cosmetic purposes [57]. Galactomyces fermentation filtrate is also an AHR-stimulant generally used in cosmetics [58]. Interestingly, epigallocatechin gallate and Galactomyces fermentation filtrate exhibit synergistic antioxidant activity against TNFα-induced ROS production (Figure 5).…”
Section: Phytogenic Antioxidantsmentioning
confidence: 99%
“…It is intriguing that FLG , OVOL1 and IL13 were the three genes most significantly associated with AD among 31 susceptible gene loci reported in a meta‐analysis of genome‐wide association studies . IL‐4R α signaling by IL‐14 and IL‐13 significantly reduced the expression of FLG, loricrin and involucrin in keratinocytes . At least two mechanisms mediate the IL‐4/IL‐13‐induced FLG down‐regulation: OVOL1 inactivation and the periostin–IL‐24 axis (Fig.…”
Section: Il‐13 and Ovol1–flg Axismentioning
confidence: 95%
“…52 IL-4Ra signaling by IL-14 and IL-13 significantly reduced the expression of FLG, loricrin and involucrin in keratinocytes. 7,[57][58][59][60] At least two mechanisms mediate the IL-4/IL-13-induced FLG down-regulation: OVOL1 inactivation and the periostin-IL-24 axis (Fig. 1).…”
Section: Il-13 and Ovol1-flg Axismentioning
confidence: 99%
“…Via activation by TCDD, the AHR decreases the permeability of the BBB in vivo [87, 88], but increased BBB permeability was observed following exposure to 3-methylcholanthrene [89]. Interestingly, though the increased BBB permeability reported by Braniste et al has not been assessed in the context of the AHR, a recent study in keratinocytes demonstrated that ligand activation of the AHR elevates occludin and claudin 1 and 4 [90], indicating that a similar AHR-mediated effect could occur in the BBB. One of the most abundant gap junction proteins in the BBB is connexin 43.…”
Section: Introductionmentioning
confidence: 99%